La petite Lili [videorecording (DVD)]. - Miller, Claude; Garcia, Nicole; Giraudeau, Bernard; Marielle, Jean-Pierre, 1932-2019-; Chekhov, Anton Pavlovich, 1860-1904 (First Run Features, 2003)
Vacationing at her summer home, actress Mado (Nicole Garcia) is joined by her lover, movie director Brice (Bernard Giraudeau), her son Julien (Robinson Stévenin) and his girlfriend, Lili (Ludivine Sagnier). Julien debuts a short film starring Lili, but Mado and Brice pan the film. Ambitious Lili runs off to Paris with Brice, who makes her a movie star. Years later, Lili contacts Julien when she hears he's about to shoot his first feature film.